Acousto-optic interaction enhancement in dual photonic-phononic cavities - N. Papanikolaou; E. Almpanis; G. Gantzounis; N. Stefanou (Proceedings of SPIE, 2012)
Light control through elastic waves is a well established and mature technology. The underlying mechanism is the scattering of light due to the dynamic modulation of the refractive index and the material interfaces caused by an elastic wave, the so-called acousto-optic interaction. This interaction can be enhanced in appropriately designed structures that simultaneously localize light and elastic waves in the same region of space and operate as dual optical-elastic cavities, often called phoxonic or optomechanical cavities. Typical examples of phoxonic cavities are multilayer films with a dielectric sandwiched between two Bragg mirrors or, in general, defects in macroscopically periodic structures that exhibit dual band gaps for light and elastic waves. In the present work we consider dielectric particles as phoxonic cavities and study the influence of elastic eigenmode vibrations on the optical Mie resonances. An important issue is the excitation of elastic waves in such submicron particles and, in this respect, we analyze the excitation of high-frequency vibrations following thermal expansion induced by the absorption of a femtosecond laser pulse. For spherical particles, homogeneous thermalization leads to excitation of the particle breathing modes. We report a thorough study of the acousto-optic interaction, correct to all orders in the acousto-optic coupling parameter, by means of rigorous full electrodynamic and elastodynamic calculations, in both time and frequency domains. Our results show that, under double elastic-optical resonance conditions, strong acousto-optic interaction takes place and results in large dynamical shifts of the high-Q optical Mie resonances, manifested through multiphonon exchange mechanisms.